Dichten in zwei Sprachen: Rilkes literarische Zweisprachigkeit aus textgenetischer Sicht - Esa Christine Hartmann (Recherches Germaniques)
Rainer Maria Rilke is one of the few world-renowned writers of the early 20th century who grew up in a multilingual and multicultural environment, learned several languages over the course of their lives, and made them their own through their literary creations. Focusing on Rilke’s multilingual and multicultural identity, this article investigates the poet’s French-German creative process by examining the various creative manifestations of his poetic bilingualism. This study explores the genesis of The Notebooks of Malte Laurids Brigge, in order to investigate Rilke’s bilingual or even translingual writing process. The genetic and poetic analysis of this genesis is based on a manuscript corpus, including the draft (“Arbeitsliste”) preceding the manuscript of the Notebooks (“Berner Taschenbuch”), the final version of the work, as well as Rilke’s notes on the French translation of the Notebooks by Maurice Betz.